2015
DOI: 10.1038/srep08517
|View full text |Cite
|
Sign up to set email alerts
|

Functional variants regulating LGALS1 (Galectin 1) expression affect human susceptibility to influenza A(H7N9)

Abstract: The fatality of avian influenza A(H7N9) infection in humans was over 30%. To identify human genetic susceptibility to A(H7N9) infection, we performed a genome-wide association study (GWAS) involving 102 A(H7N9) patients and 106 heavily-exposed healthy poultry workers, a sample size critically restricted by the small number of human A(H7N9) cases. To tackle the stringent significance cutoff of GWAS, we utilized an artificial imputation program SnipSnip to improve the association signals. In single-SNP analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 47 publications
0
35
1
4
Order By: Relevance
“…To identify host susceptibility gene to severe influenza, we previously conducted genome‐wide association studies (GWAS) in two study cohorts: the H7N9 cohort including H7N9 patients versus healthy controls who were heavily exposed to the virus (Chen et al , ), and the H1N1 cohort consisting of severe H1N1 patients versus control patients with mild H1N1 infection (Zhou et al , ). To prioritize the candidate susceptibility genes to H7N9 and severe H1N1 infection, we integrated the GWAS discovery with expression quantitative trait loci (eQTL) analysis, a strategy which has been widely used to identify the trait gene targets (Musunuru et al , ; Zhu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…To identify host susceptibility gene to severe influenza, we previously conducted genome‐wide association studies (GWAS) in two study cohorts: the H7N9 cohort including H7N9 patients versus healthy controls who were heavily exposed to the virus (Chen et al , ), and the H1N1 cohort consisting of severe H1N1 patients versus control patients with mild H1N1 infection (Zhou et al , ). To prioritize the candidate susceptibility genes to H7N9 and severe H1N1 infection, we integrated the GWAS discovery with expression quantitative trait loci (eQTL) analysis, a strategy which has been widely used to identify the trait gene targets (Musunuru et al , ; Zhu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1, we present some representative identified KEGG pathway terms. The pathway "ECM-receptor interaction" was found significantly enriched in two Influenza A related studies [23,24]. It has been reported that cellular processes such as adhesion, dynamic behaviors and apoptosis, regulated by ECM-receptor interaction, influence the entry or replication of influenza viruses [23].…”
Section: Resultsmentioning
confidence: 99%
“…The pathway "ECM-receptor interaction" was found significantly enriched in two Influenza A related studies [23,24]. It has been reported that cellular processes such as adhesion, dynamic behaviors and apoptosis, regulated by ECM-receptor interaction, influence the entry or replication of influenza viruses [23]. Regarding "TGF-b signaling", it has been shown that respiratory viral infections offset secretion of TGF-β which in turn is implicated in decreasing pulmonary inflammation and extending host survival [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Carriage of LGALS1 rs4820294/rs2899292 haplotype GG was associated with protection from A(H7N9) virus infection in humans. Furthermore, rs4820294/rs2899292 haplotype GG was correlated with higher levels of LGALS1 mRNA and protein expression in lymphoblast cell lines [24 ]. Therefore, the differential LGALS1 expression may contribute to the distinct susceptibility of some individuals to human A(H7N9) influenza.…”
Section: Antimicrobial Molecules In the Airwaymentioning
confidence: 97%